Study on Quality of Life of Patients with Obstructive Sleep Apnea—Pilot Study - Olja Tanellari; Brunilda Koci; Edlira Baruti Papa; Carina Balcos; Adina Oana Armencia; Tinela Panaite; Irina Zetu (Medicina)
Background and Objectives: Sleep apnea (OSA) significantly impacts patients’ health, affecting cognitive, emotional, and social functioning, thus reducing overall quality of life (QoL). Despite global research interest, there are limited data on the QoL of Romanian patients with OSA. Aim of study: This study aimed to assess the quality of life of patients diagnosed with OSA using the Sleep Apnea Quality of Life Index (SAQLI), a validated, disease-specific questionnaire. Material and Methods: A cross-sectional study was conducted between January 2021 and February 2022 on 28 adult patients from medical units in Iași (Romania) and Albania. The patients were clinically evaluated and confirmed to have OSA (AHI > 5). QoL was assessed pre-treatment using the SAQLI, covering daily activities, social interactions, emotional status, and symptomatology. Statistical analyses were performed using SPSS v26.0. Results: Most patients had moderate (32.1%) or severe OSA (53.6%). Lower QoL scores correlated with increased disease severity. Significant impairments were observed in daily functioning, social relationships, and emotional well-being. Patients with severe OSA reported the lowest scores across all domains. Conclusions: OSA severely affects quality of life, particularly in patients with moderate to severe forms. Early diagnosis and personalized, multidisciplinary management strategies are essential to improving outcomes and overall patient well-being.